2006
DOI: 10.1111/j.1746-1561.2006.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergens in School Settings: Results of Environmental Assessments in 3 City School Systems

Abstract: Environmental allergens are major triggers for pediatric asthma. While children's greatest exposure to indoor allergens is in the home, other public places where children spend a large amount of time, such as school and day care centers, may also be sources of significant allergen encounters. The purpose of this article is to describe schoolroom allergen levels from 3 different geographic sites obtained from dust samples collected in the fall and in spring. Environmental dust samples were collected from elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 8 publications
0
51
2
Order By: Relevance
“…Cat and dog allergen are nearly ubiquitous in indoor spaces, and many studies have detected their presence in places not containing or permitting pets, particularly schools and daycare centers [3,[28][29][30]. Pet allergen is mainly carried into classrooms on the garments of pet owners, and the amount of cat allergen in a school has been shown to be proportional to the number of cat owners in class [30].…”
Section: Exposure Mitigationmentioning
confidence: 98%
“…Cat and dog allergen are nearly ubiquitous in indoor spaces, and many studies have detected their presence in places not containing or permitting pets, particularly schools and daycare centers [3,[28][29][30]. Pet allergen is mainly carried into classrooms on the garments of pet owners, and the amount of cat allergen in a school has been shown to be proportional to the number of cat owners in class [30].…”
Section: Exposure Mitigationmentioning
confidence: 98%
“…In the studied facilities, the highest average concentrations were detected in Brazil and in some humid regions in the United States. [10][11][12] In contrast, very low dust mite allergen levels have been found in colder and drier climates. [13][14][15] Average yearly humidity in İzmir is 57.9%.…”
Section: Distributions Of Allergensmentioning
confidence: 99%
“…13,16,24,26 However, this relationship with carpeted floor was not present in all studies. 11 Although mite levels tend to exhibit seasonal fluctuations that parallel those in ambient relative humidity, additional factors, including human activities and heating, ventilation, and air conditioning may also influence indoor air humidity levels. 3 In keeping with this data, we found that Der p 1 concentration was higher in DCs with air-condition system for ventilation (0.67 µg/g vs. 0.45 µg/g; p=0.008).…”
Section: Distributions Of Allergensmentioning
confidence: 99%
“…Similarly high exposure to pyroglyphid mites was found in Polish and US libraries (28,32) and in New Zealand and UK cinemas (24,33); most dust samples exceeded the sensitisation threshold. In Polish libraries, the main source of mites were bookshelves, books, and upholstered chairs.…”
Section: Exposure To House Dust Mites In Public/occupational Settingsmentioning
confidence: 99%
“…hotel chambermaids High Cinemas (24,33) all staff Moderate Fishing-boats (38) fi shermen Moderate Submarines, ships (39) all crew Moderate Libraries (28,32) librarians, cleaners Moderate Schools (46,47) teachers, cleaners Low-moderate* Day care centres (46) day care workers Low-moderate* Offi ces (20,21) offi ce workers, cleaners Low Churches (24) priests Low Airplanes (24) all crew Low Buses, trains, trams, taxies (34)(35)(36)(37) all crew Low Poultry farms (43) poultry farm workers Low …”
mentioning
confidence: 99%